MacchiariniGate: The Fall from Grace of Stem Cell Healer, Paolo Macchiarini, and Clues and Concerns from the Early Literature that Cast Ethical Doubts - da Silva, Jaime A. Teixeira (Bangladesh Journal of Bioethics, 2018)
After a long and successful career in tracheal surgery and lung cancer, Paolo Macchiarini became very famous in 2008 with the transplantation of a trachea from a cadaver that then apparently used the patient’s own stem cells to supposedly regenerate new trachea, i.e., tissue-engineered tracheae. Among the nine patients that received this revolutionary treatment, using biological or artificial tracheae, under Macchiarini’s supervision, six have reportedly died. Although several critics had expressed concerns with the procedures, allegations of misconduct against Macchiarini first arose in August of 2014 by four Karolinska Institutet (KI) colleagues, and an independent investigation was called for by KI based on claims made in seven published papers. Among the claims were the fact that the procedure constituted a high risk, information on the patients was incomplete and that there was no or incomplete ethical approval, thus constituting misconduct. His CV was also shown to contain inaccuracies. By September 10, 2016, most of these claims have now proved to be true, and Macchiarini was found guilty of misconduct by KI. This paper looks primarily at earlier published papers by Macchiarini and his collaborators in a search for clues to better understand the evolution of altruism, or narcissism. An assessment of the controversial papers, and of letters written by critics and skeptics like Pierre R. Delaere, indicate that insufficient experimental evidence was presented for several case studies, and that claims made about the success of the procedures exceeded what was shown by the evidence. A domino effect of personal and professional tragedies ensued, in rapid succession, between 2014 and 2016. The effect on the field of stem cell research has been chilling, and the side-effects have taken their toll, with several high-profile resignations, primarily at KI, within the Swedish education system and in the Nobel Committee. This case has mesmerized the bioethics and biomedical communities for years.